DETERMINING MATURITY RATE OF HYDROCARBON USING SAMPLE CORE FROM GEOCHEMISTRY SURVEY IN PADAMARANG SUB-BASIN, BONE GULF, SOUTH OF SULAWESI - Pusparini, Widyatri; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2019)
Sulawesi is one of the area in Eastern Indonesia that still has frontier area. South Sulawesi has several basins which formed as a result of tectonic activity that caused a geological condition complexity. The complexity of the regional geology is one of the interest of this research. The presence of gas seep within research area ensure that there is a potential petroleum system underneath the surface of the research area which is Padamarang sub-Basin, Bone Basin, South of Sulawesi. New insights into Bone Gulf is based on surface geochemical exploration that came up with 26 core sea sediments samples using piston core acquisition that has been analyzed with Gas Chromatography in sediment extract.  This study aims to identify the geochemical characteristics of migrated hydrocarbon. These geochemistry characteristics referred to depositional environment and maturity determination that are analyzed using non biomarker parameters including CPI and OEP, and cross plot between CPI and Pr/Phy. According to the CPI value has shown the number from 0.169 to 1.27 with the majority of the values is 0.4. While OEP value has shown the number from 0.312 to 1.5 with the majority of the values is 0.75.  Thus, according to the majority value of CPI and OEP, we could determine that it was thermally immatured.Keywords: Biomarker, Core, Geochemical, Non Biomarker, Padamarang